AtHsc70‐1 negatively regulates the basal heat tolerance in Arabidopsis thaliana through affecting the activity of HsfAs and Hsp101. (16th July 2020) - Tiwari, Lalit D.; Khungar, Lisha; Grover, Anil
Summary: Heat shock protein 70 (Hsp70) chaperones are highly conserved and essential proteins with diverse cellular functions, including plant abiotic stress tolerance. Hsp70 proteins have been linked with basal heat tolerance in plants. Hsp101 likewise is an important chaperone protein that plays a critical role in heat tolerance in plants. We observed that Arabidopsis hsc70‐1 mutant seedlings show elevated basal heat tolerance compared with wild‐type. Over‐expression of Hsc70‐1 resulted in increased heat sensitivity. Hsp101 transcript and protein levels were increased during non‐heat stress (HS) and post‐HS conditions in hsc70‐1 mutant seedlings. In contrast, Hsp101 was repressed in Hsc70‐1 over‐expressing plants after post‐HS conditions. Hsc70‐1 showed physical interaction with HsfA1d and HsfA1e protein in the cytosol under non‐HS conditions. In transient reporter gene analysis, HsfA1d, HsfA1e and HsfA2 showed transcriptional response on the Hsp101 promoter. HsfA1d and HsfA2 transcripts were at higher levels in hsc70‐1 mutant compared with wild‐type. We provide genetic evidence that Hsc70‐1 is a negative regulator affecting HsfA1d/A1e/A2 activators, which in turn regulate Hsp101 expression and basal thermotolerance. Significance Statement: Tiwari et al . provide genetic evidence showing that Hsc70‐1 is a negative regulator of heat shock transcription factors, and its absence leads to enhanced Hsp101 expression resulting in plants with high basal thermotolerance.